Influence of subclinical corneal edema on contrast sensitivity in fuchs endothelial corneal dystrophy - Friedrich, Maximilian; Hofmann, Christina Antonia; Chychko, Lizaveta; Son, Hyeck Soo; Khoramnia, Ramin; Auffarth, Gerd U.; Augustin, Victor A. (Cornea, 2024)
Purpose: The aim of this study was to compare visual function, with a focus on contrast sensitivity, between patients with Fuchs endothelial corneal dystrophy (FECD) with and without subclinical corneal edema.Methods: In this cross-sectional, observational, single-center study, 46 pseudophakic eyes of 31 patients with FECD were divided into 2 groups depending on the presence of subclinical corneal edema. All eyes presented with a Krachmer grade of 5 and no clinical corneal edema. The criteria for subclinical corneal edema were loss of regular isopachs, displacement of the thinnest point, and focal posterior surface depression in Scheimpflug tomography. If more than 1 criterion was present, subclinical corneal edema was diagnosed. The corrected distance visual acuity, contrast sensitivity (Pelli-Robson chart and CSV-1000 test with optional glare), and straylight were measured. The differences between both groups were analyzed using clustered Wilcoxon rank-sum tests. Results: The corrected distance visual acuity and the contrast sensitivity, measured with a Pelli-Robson chart, were significantly inferior in eyes with subclinical corneal edema compared with eyes without subclinical edema (P < 0.05). At all spatial frequencies, eyes with subclinical edema demonstrated lower contrast sensitivity with a statistically significantly reduction in total contrast sensitivity when tested with (P = 0.005) and without (P = 0.002) glare. The straylight did not significantly differ between both groups (P > 0.05). Conclusions: The corrected distance visual acuity and contrast sensitivity were significantly reduced in FECD eyes with subclinical corneal edema compared with those with no subclinical edema. This decrease in visual quality may be considered when evaluating the need for surgical intervention at earlier stages of FECD.